HUBUNGAN KEKUATAN OTOT TUNGKAI DENGAN AKURASI SHOOTING KE GAWANG DALAM PERMAINAN SEPAK BOLA PADA MAHASISWA PUTRA KEPELATIHAN 2 A PENDOR KIP UNIVERSITAS RIAU - Hadi, Irwan; ', Slamet; ', Saripin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem in this research is to investigate the relationship Muscle Strength Legs With Accuracy Shooting Kegawang In Game Football On Student Son Coaching 2 A PENDOR FKIP Riau University totaling 27 people by using total sampling technique in which all the population sampled, to obtain research data used Test leg Dynamometer, and precision kicking the ball (shooting) toward the goal. Sampling technique used is purposive sampling. Data obtained from tests Leg Dynamometer highest data that is 192.5 kilograms and 77.5 kilograms of the data room, average 118.11, 28.66 standard definition. and the data obtained from the accuracy kicking the ball (shooting) to the wicket 142.85 the highest value and the lowest value of 71.98, an average of 100.0 with a standard deviation of 15.88. The maximum value is denoted L0 observation Lilifors max, where the value L0maks <Ltabel the samples come from populations with normal distribution. Based on the analysis of data obtained by the correlation coefficient of r = -0.137 where r table = 0.381, means that Ho is accepted and Ha rejected. Thus, it means there is no relationship between leg muscle strength with accuracy kicking the ball (shooting) toward the goal. Having carried out research which starts from data collection to data processing that is eventually used as a benchmark as a discussion of the research results. Leg muscle strength (X) does not have a significant relationship with the precision of kicking a ball (shooting) toward the goal (Y) on the student's coaching 2A Riau University.Keywords: leg muscle strength, accuracy of kicking the ball (shooting) toward the goal